KINERJA GURU TIDAK TETAP DAN EFEKTIVITAS PEMBELAJARAN - Sheila Hentri Utami; Abdul Rahman; Baryanto Baryanto (Institut Agama Islam Negeri (IAIN) Bone, 2020)
Teacher is a noble profession. That is why teachers are often called the unsung heroes. It is because of teachers; a nation can develop and be civilized along with the development of other nations. In carrying out the mandate as the frontline in educating children of the nation, teachers are required to have high professionalism. However, such a point does not go hand in hand with the welfare efforts made for them, especially for those of the non-permanent teachers. Anchored in this assumption, this study sought to find out a depiction of learning effectiveness held by the non-permanent teachers at SMA 1 Muhammadiyah Curup, Bengkulu. This study applied a qualitative approach. Observation and interviews were deployed as the data collection tools. The data were further analyzed qualitatively. The conclusion revealed that the status of being non-permanent teachers did not reduce the effectiveness of their performance in carrying out their duties as teachers albeit in the midst of uncertain and incompatible salary compared to the whole services they provided and the lack of learning facilities at the school. Keywords: learning effectiveness, professionalism, non-permanent teachers